(untitled) (Metallurgy and Foundry Engineering, 2011)
The article takes into consideration the researches concerning inserting the Glassex additive to the moulding sands with water glass and the new ester hardeners. The investigations combine the works connected to the Glassex additive influence on the moulding sand’s with water glass knock-out properties and the works connected to the elaboration of the new ester hardeners upgrading of ability to mechanical reclamation of the moulding sand with water glass.